2020
DOI: 10.1002/hbm.24934
|View full text |Cite
|
Sign up to set email alerts
|

The association between resting‐state functional magnetic resonance imaging and aortic pulse‐wave velocity in healthy adults

Abstract: Resting-state functional magnetic resonance imaging (rs-fMRI) is frequently used to study brain function; but, it is unclear whether BOLD-signal fluctuation amplitude and functional connectivity are associated with vascular factors, and how vascularhealth factors are reflected in rs-fMRI metrics in the healthy population. As arterial stiffening is a known age-related cardiovascular risk factor, we investigated the associations between aortic stiffening (as measured using pulse-wave velocity [PWV]) and rs-fMRI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 82 publications
2
23
0
Order By: Relevance
“…Besides the DWMN and DAN, normal aging was associated with RFC increase in the sensorimotor, subcortical network, and para-hippocampal cortex. This has also been reported previously [40, 45, 46, 48, 51, 54] . We didn’t find significant age-related RFC declines in precuneus and specific sub-regions of the hippocampal cortex as reported in previous studies [40, 41] .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Besides the DWMN and DAN, normal aging was associated with RFC increase in the sensorimotor, subcortical network, and para-hippocampal cortex. This has also been reported previously [40, 45, 46, 48, 51, 54] . We didn’t find significant age-related RFC declines in precuneus and specific sub-regions of the hippocampal cortex as reported in previous studies [40, 41] .…”
Section: Discussionsupporting
confidence: 90%
“…This is likely to be the reason why the linear regressions of the RFC metrics with the adult age depict substantial scatters and relative low correlation coefficients. The impact of the potential confounds and pre-processing strategies that can mitigate them have been extensively investigated in the published literature [2733, 45, 46] . Here we focus on comparing our findings in the context of documented literature results, particularly the adult age effect in the DMN, dorsal attention network (DAN), sensorimotor network and subcortical brain regions.…”
Section: Discussionmentioning
confidence: 99%
“…The blood oxygen level-dependent (BOLD) signal in functional MRI (fMRI) has mainly been used to measure very low frequency (VLF) hemodynamic responses to neuronal activity oscillations. However, the BOLD signal is also an indicator of basic underlying vascular and respiratory factors in the brain 19 23 . Recent research has indicated an elevated variability in the BOLD signal, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, it needs to be further explored if the observed VRF-related changes in RSFC reflect changes in blood flow, changes in neuronal activity or both. 68 Fifth, levels of cerebral AD-related PET biomarkers were low to moderate in our relatively young cohort and the sample size was limited, therefore, associations of Ab and tau with longitudinal RSFC may have been harder to detect.…”
Section: Discussionmentioning
confidence: 84%